Cotton pulp for bone tissue engineering. Issue 16 (1st November 2020) - Singh, Sandhya; Dutt, Dharm; Mishra, Narayan Chand
Abstract: Cellulose, a polysaccharide of β (1–4) linked D-glucose units, is a cheap, eco-friendly and most abundant natural polymer on this planet. Among various cellulosic materials, cotton cellulose is readily available, lignin-free, FDA approved, and widely used in the medical field because of its higher degree of biocompatibility and non-cytotoxic nature. Though cotton cellulose showed essential material properties for scaffold design, the least priority had been given to this material. The present study aimed at exploring the fabrication of scaffold using cotton microfibers for bone tissue engineering application. The study also aimed at improving the mechanical, physio-chemical and osteogenic properties of the microfibrous scaffold by crosslinking with citric acid and further modified with gelatin. FTIR indicated some interactions between cellulose, citric acid and gelatin within the scaffolds, while XRD results demonstrated the crystalline nature of scaffolds. Porosity and swelling studies demonstrated that all scaffolds are hydrophilic and porous. The microporous interconnected network of scaffolds was confirmed by FESEM. FESEM micrographs and MTT assay confirmed that all scaffolds were nontoxic to MG 63. Based on findings, it was concluded that gelatin coated cotton cellulose microfibers crosslinked with citric acid scaffold would be a potential template for bone tissue engineering.